Herbertiidae (Hymenoptera: Chalcidoidea): a family previously unrecorded in the Middle East - Hossein Lotfalizadeh; Ali Ameri; Mohammadreza Nematian (نامه انجمن حشره‌شناسی ایران, 2025)
During a faunistic study of mangrove habitats conducted between 2015–2019 along the Makran coast (southeastern Iran), we collected specimens initially classified under the former Pteromalidae (Hymenoptera: Chalcidoidea). These were identified as Herbertia wallacei Burks, 1959 (Hymenoptera: Herbertiidae). This represents the first record of H. wallacei in Iran and the first documentation of the family Herbertiidae in the Middle East.